Pengaruh Pengetahuan Orangtua/Wali Terhadap Kepatuhan Imunisasi Dasar Di Poliklinik Anak RSPAD Gatot Soebroto - Bibit Bilawati; Dwi Agutina (Jurnal Persada Husada Indonesia, 2016)
Basic immunization compliance is influenced by several factorswhich included parents/guardians’ knowledge. This study is aimed to find out how the knowledge factor influences parents/guardians’ compliance in taking infants for basic immunization. This study was carried out at RSPAD Gatot Subroto Pediatric Polyclinic in March 2016 with a total population of 35 parents/guardians. This study used descriptive method with cr4oss sectional approach. Questionaires on knowledge were distributed to respondents and immunization compliance recorded through KMS (Towards Health Card) observation. Chi Square analysis showed p value of 0.04 showing strong influence between parents/guardians’ knowledge on immunization and parents/gua rdians’ compliance in bringing children to be immunized. Education on immunization is very important to be given to parents/guardians at every visitation and this aspect need to be facilitated by the hospital.